A Concise Review on the Role of Endoplasmic Reticulum Stress in the Development of Autoimmunity in Vitiligo Pathogenesis - Jadeja, Shahnawaz D.; Mayatra, Jay M.; Vaishnav, Jayvadan; Shukla, Nirali; Begum, Rasheedunnisa (Frontiers in Immunology, 2021)
Vitiligo is characterized by circumscribed depigmented macules in the skin resulting due to the autoimmune destruction of melanocytes from the epidermis. Both humoral as well as cell-mediated autoimmune responses are involved in melanocyte destruction. Several studies including ours have established that oxidative stress is involved in vitiligo onset, while autoimmunity contributes to the disease progression. However, the underlying mechanism involved in programing the onset and progression of the disease remains a conundrum. Based on several direct and indirect evidences, we suggested that endoplasmic reticulum (ER) stress might act as a connecting link between oxidative stress and autoimmunity in vitiligo pathogenesis. Oxidative stress disrupts cellular redox potential that extends to the ER causing the accumulation of misfolded proteins, which activates the unfolded protein response (UPR). The primary aim of UPR is to resolve the stress and restore cellular homeostasis for cell survival. Growing evidences suggest a vital role of UPR in immune regulation. Moreover, defective UPR has been implicated in the development of autoimmunity in several autoimmune disorders. ER stress-activated UPR plays an essential role in the regulation and maintenance of innate as well as adaptive immunity, and a defective UPR may result in systemic/ tissue level/ organ-specific autoimmunity. This review emphasizes on understanding the role of ER stress-induced UPR in the development of systemic and tissue level autoimmunity in vitiligo pathogenesis and its therapeutics.